Ozone rectal insufflation inhibits the development of atherosclerosis in ApoE−/−mice, which is mediated by the regulation of gut microbiota and metabolites - Li, Ruihua; Wang, Yulin; Ji, Xuelian; Han, Qi; He, Kang; Zhao, Haobin; Li, Hongbo (Frontiers in Microbiology, 2025)
IntroductionAtherosclerotic cardiovascular disease is the world’s leading cause of death. Researches have proven that ozone therapy can effectively inhibit the development of atherosclerosis; however, the underlying mechanisms remain unclear. This study aims to explore how ozone rectal insufflation (O3-RI) prevents atherosclerosis.MethodsO3-RI therapy involves administering medical ozone via rectal injection to prevent multiple diseases. ApoE−/− mice were fed a high-fat diet (HFD) to induce atherosclerosis. Gut microbiota was identified by 16S rRNA sequencing. Microbial metabolites were determined by liquid chromatography-mass spectrometry(LC–MS).ResultsO3-RI reduced serum LDL-C levels by approximately 29.6% and decreased both atherosclerotic lipid areas and plaque area in ApoE−/− mice. Additionally, O3-RI improved gut microbiota imbalance caused by a high-fat diet in these mice. Notably, O3-RI increased beneficial microorganisms like Lactobacillus and Bifidobacterium, which help reduce atherosclerosis. Additionally, O3-RI also increased the levels of short-chain fatty acids, such as propionic acid and butyric acid, At the same time, it decreased harmful microbial metabolites, like TMA and TMAO in fecal samples.DiscussionThis research indicates that O3-RI effectively inhibits atherosclerosis and reduces serum LDL-C levels. These effects are likely linked to ozone’s optimization of gut microbiota and regulation of microbial metabolites in ApoE−/− mice. The non-invasive O3-RI may play a crucial role in managing and treating atherosclerosis. The non-invasive O3-RI may play a crucial role in the managing and treating of atherosclerosis.